"Should I stay or should I go?"—Why the future of global work may be less binary: Lessons on approaches to global crises from the experiences of expatriates during the COVID‐19 pandemic. (9th August 2022) - Végh, Judit; Jenkins, Joyce; Claes, Marie‐Therese
Abstract: COVID‐19 has significantly impacted expatriates, affecting their ability to work effectively and their personal and family lives. This study explores their experiences in different phases of the pandemic, and their perspectives on the future of international living in light of such global disruption. Involving over 600 expatriates in 48 countries, the research shows shifts in motivation and priorities as a result of the crisis and reveals how family (extended and immediate) topped expatriates' concerns. The study examines if and how support systems worked and looks at coping mechanisms, skills, traits, previous experience, and attitudes which participants found useful. A common theme was "falling between two stools"—where expatriates were ineligible for support in either their home country or in their host country. Others described being "pulled in different directions" or "torn by a dilemma" with pros and cons in either choice. The study contributes to the questions about the future of global work with results of the survey revealing changing norms for expatriation and global mobility raising the possibility of more nuanced approaches to global projects and less binary options for global professionals and their families.